Facial Emotion Perceptual Tendency in Violent and Non-violent Offenders - Zeng, Yun (Journal of interpersonal violence, 2022)
All three authors share equal authorship in this paper.Emotion perception has a vital influence on social interaction. Previous studies discussed mainly the relationship between facial emotion perception and aggressive behavior from the perspective of hostile attributional bias and the impaired violence inhibition mechanism. The present study aims to provide new evidence of different emotion perception patterns between the violent and non-violent criminal samples through a new indicator of the facial emotion recognition test, Facial Emotion Perception Tendency (FEPT), calculated by counting the times a participant recognizes a set of emotional stimuli as a particular specific emotion, and to further examine the association between aggressive behaviors and FEPT. 101 violent and 171 non-violent offenders, as well as 81 non-offending control participants, were recruited to complete the emotion recognition task with morphed stimuli (Study 1). We further recruited 62 non-offending healthy male participants to finish the Buss -Perry Aggression Questionnaire (BPAQ) after the emotion recognition task in Study 2. Both non-violent and violent offenders were significantly lower in overall accuracy of emotion recognition and disgust FEPT, but higher in happy FEPT, than non-offending healthy controls. Non-violent offenders had significantly lower fear FEPT than violent offenders, and had higher anger FEPT than non-offending controls. The results also revealed that the level of physical aggression was positively correlated with fear FEPT, while negatively correlated with anger FEPT. The current study demonstrated that FEPT was associated with aggressive behavior and implies the importance of improving the emotion decoding ability of offenders. Also, the concept ?FEPT? proposed in this study is of significance for further exploration of how individuals? tendency to perceiving a particular emotion can be correlated with social behaviors.